Relationship of Students’ Activities, Responses, and Cognitive Learning Outcomes on Natural Science Learning-Based Ethno-STEM in Secondary School - Septi Budi Sartika; Nur Efendi; Fitria Eka Wulandari (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
The research aims to describe the relationship of students' activities, responses, and cognitive learning outcomes in natural science learning based ethno-STEM in secondary school. Research methods use quantitative approaches with this type of correlation research. The population and research sample are class VIII students at SMP Muhammadiyah 5 Tulangan Sidoarjo. Data collection techniques use questionnaires and documentation. Questionnaires are used to determine students' activities and responses during natural science learning based ethno-STEM. Documentation in the form of documented student learning test results. In the study results test used cognitive learning results that refer to Bloom's C4 taxonomy, namely analytical thinking skills. Data analysis techniques use descriptive statistics that use SPSS-assisted product-moment correlation tests. The results showed that in the implementation of natural science learning based ethno-STEM there was a weak relationship between: 1) there is an activity relationship to students' cognitive learning outcomes with a contribution of 0.2%, 2) there is a response relationship to student cognitive learning outcomes with a contribution of 0.9%, and 3) there is a relationship of activity and response to student cognitive learning outcomes with a contribution of 1%. There are allegations that other variables also affect students' cognitive learning outcomes, these variables need to be revealed through further.